2013
DOI: 10.3750/aip2013.43.4.11
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of great white shark, <I>Carcharodon carcharias</I> (Elasmobranchii: Lamniformes: Lamnidae), off Corsica (northern Mediterranean): historical and contemporary records

Abstract: Group (Corsica-MSRG), in order to assess the present status of its population around Corsica. The actions of the group have been supported by local fishermen actively helping the researchers in reporting relevant sightings and collection of the specimens. In the wake of this cooperation, on 30 August 2012, we were informed that a male specimen of Carcharodon carcharias was captured by trammel-nets, at a depths range of 190 and 200 m, by 42°29′09.02′′N and 8°34′79.20′′E (Fig. 1, record 11), together with decapo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 4 publications
1
2
0
Order By: Relevance
“…However, most of these records occurred in the central Mediter ranean, especially in the Strait of Sicily, where several juvenile and adult specimens were recorded (Fergus son 1996(Fergus son , 2002De Maddalena et al, 2002;De Mad dalena, 2006;Saïdi et al, 2005a). Similar patterns were confirmed by Maliet et al (2013) who pointed out the relative abundance of captures of C. carcharias throughout the Corsican coast and the adjacent areas.…”
Section: Great White Shark Carcharodon Carchariassupporting
confidence: 80%
See 1 more Smart Citation
“…However, most of these records occurred in the central Mediter ranean, especially in the Strait of Sicily, where several juvenile and adult specimens were recorded (Fergus son 1996(Fergus son , 2002De Maddalena et al, 2002;De Mad dalena, 2006;Saïdi et al, 2005a). Similar patterns were confirmed by Maliet et al (2013) who pointed out the relative abundance of captures of C. carcharias throughout the Corsican coast and the adjacent areas.…”
Section: Great White Shark Carcharodon Carchariassupporting
confidence: 80%
“…4). This new capture of a great white in northern Tunisian waters shows that the central Mediterranean is probably a nursery area for the species in total accor dance with Maliet et al (2013) and Bradaï and Saïdi (2013).…”
Section: Great White Shark Carcharodon Carchariasmentioning
confidence: 81%
“…Akyol et al (2011) Kabasakal et al (2011) and Kabasakal (2013). Additionally, Kabasakal and Gediko glu (2008) and Kabasakal et al (2009) found new-born and juvenile C. carcharias in Turkish waters, such observations suggesting that Turkish waters could be considered as a nursery area for the species, as appears to be the case in the central Mediterranean (Sa€ ıdi et al, 2005;Maliet et al, 2013). This suitable hypothesis needs further observation, but cannot be totally ruled out.…”
Section: Resultsmentioning
confidence: 97%